Could an Impairment in Local Translation of mRNAs in Glia be Contributing to Pathogenesis in ALS? - Barton, Samantha K.; Gregory, Jenna M.; Chandran, Siddharthan; Turner, Bradley J. (Frontiers in Molecular Neuroscience, 2019)
One of the key pathways implicated in amyotrophic lateral sclerosis (ALS) pathogenesis is abnormal RNA processing. Studies to date have focussed on defects in RNA stability, splicing, and translation, but this review will focus on the largely overlooked RNA processing mechanism of RNA trafficking, with particular emphasis on the importance of glia. In the central nervous system (CNS), oligodendrocytes can extend processes to myelinate and metabolically support up to 50 axons and astrocytes can extend processes to cover up to 100,000 synapses, all with differing local functional requirements. Furthermore, many of the proteins required in these processes are large, aggregation-prone proteins which would be difficult to transport in their fully translated, terminally-folded state. This therefore highlights a critical requirement in these cells for local control of protein translation, which is achieved through specific trafficking of mRNAs to each process and local translation therein. Given that a large number of RNA-binding proteins have been implicated in ALS, and RNA-binding proteins are essential for trafficking mRNAs from the nucleus to glial processes for local translation, RNA misprocessing in glial cells is a likely source of cellular dysfunction in ALS. To date, neurons have been the focus of ALS research, but a cell autonomous deficit in glia, namely astrocytes and oligodendrocytes, could have an additive effect on declining neuronal function in ALS. This review aims to highlight the key evidence that supports the contention that RNA trafficking deficits in astrocytes and oligodendrocytes may contribute to in ALS.